Coral reefs management and decision making tools. (1st September 2017) - Hilmi, Nathalie; Safa, Alain; Sumalia, U. Rashid; Cinar, Mine
Abstract: In this article, we examine the problem of coral reef destruction and discuss various stakeholders who suffer losses from the destruction. We then postulate a stakeholder versus threats matrix and outline an algorithm where public authorities can streamline policy based on expected losses. We also formulate, using local data, divergence between public good and individual benefits and examine the agent behaviour under monitoring. Our examples, using previous estimations on net benefits, give guidelines on how to form public policy and management strategies. Highlights: Natural resource management concerns both people and natural resources. As coral reefs are considered as a common property, we apply a community-based natural resource management. Profit-loss matrices assess damages under uncertainty per stakeholder or per threat source. Payoff matrices and Nash equilibrium strategy in game theoretical model give indications to policy-makers.